(untitled) (FULafia Journal of Science and Technology, 2020)
Governance capacity determines the effectiveness of urban environments and systems. Thus, unplanned landscapes and poor land management as commonly observed in Nigeria’s cities, are a reflection of poor governance. This has led many researchers to conclude that these spaces are characterised by the “absence” of public sector governance. Following the 2016 World Health Organisation declaration of Aba and Onitsha amongst the world’s 20 worst cities by air quality, this paper reviews environmental problems in these functionally similar locations to ascertain the “presence” or “absence” of governance in their respective environments. Data for the study was obtained from secondary sources: published literature, substantive news articles, the archives and from the authors’ field observations.